Bagaimana Gender, Risk, dan Media terhadap Pengungkapan Corporate Social Responsibility? - Wahdan Arum Inawati; Aufa Oktafitria (Owner : Riset dan Jurnal Akuntansi, 2023)
This study focused to analyze relationship between gender diversity, risk minimization and media exposure on corporate social responsibility disclosure. In this study consists of independent variables, dependent variable and control variable. Researcher used profitability with ROA as proxy as a control variable in this study. Quantitative research in this study applied companies in the Basic Materials sector listed on the Indonesia Stock Exchange (IDX) in 2018-2021. Some criterions determined by researcher to obtain sample in this study. Non-probability sampling used in this study and researcher decided ten companies with a four-year observation period to obtain 40 observation units. Panel data regression as data analysis technique and used Eviews 12 software. The results of this study, simultaneously gender diversity, risk minimization and media exposure with the control variable profitability affect corporate social responsibility disclosure with a probability value (F-statistic) of 0.000078 <0.05 so that H01 is rejected and Ha1 is accepted.. Partially, that risk minimization and media exposure with the control variable profitability have a positive effect on corporate social responsibility disclosure with a probability value <0.05 so that H03 and H04 are rejected, it means that Ha3 and Ha4 are accepted. Meanwhile, gender diversity has no effect on the corporate social responsibility disclosure. This means that the presence of female board members in this percentage is still unable to influence corporate social responsibility disclosure.